2020
DOI: 10.1002/bjs.11425
|View full text |Cite
|
Sign up to set email alerts
|

Network meta-analysis of local and regional analgesia following colorectal resection

Abstract: Background Postoperative pain management after colorectal surgery remains challenging. Systemic opiates delivered on demand or via a patient‐controlled pump have traditionally been the mainstay of treatment. Opiate analgesia is associated with slower gastrointestinal recovery and unpleasant side‐effects; many regional and local analgesic techniques have been developed as alternatives. Methods MEDLINE, Embase and CENTRAL databases were searched systematically for RCTs comparing analgesic techniques after major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Local injections at the sites of pain are widely used as an effective treatment strategy for rapid pain relief in various conditions and local nerve blocks are highly effective for postsurgical analgesia (18). Several studies have recommended combination therapy with local anesthetics (for their rapid analgesic effects) and corticosteroids (for their slower but longer-acting action), and such combinations have often been used in clinical studies (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Local injections at the sites of pain are widely used as an effective treatment strategy for rapid pain relief in various conditions and local nerve blocks are highly effective for postsurgical analgesia (18). Several studies have recommended combination therapy with local anesthetics (for their rapid analgesic effects) and corticosteroids (for their slower but longer-acting action), and such combinations have often been used in clinical studies (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The basic accepted principles for multimodal analgesia are the relief of pain while reducing opioid consumption and potential risk/side effects from the medications. 19 This study aimed to examine 2 components of a multimodal analgesia regimen by comparing 2 possible routes of administering local anesthetic to find out which technique should be incorporated in the analgesia regimes. This study showed a significant reduction of opioid consumption, but similar pain scores, in the IPL group when compared to the IVL group.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent network meta-analysis, Xu et al [44] compared local and regional anaesthetic techniques in colorectal patients, demonstrating the superiority of TAP blocks and spinal anaesthesia over other techniques. Given the findings by Xu et al, the potential to prolong the effect of TAP blocks using LB would be particularly advantageous.…”
Section: Discussionmentioning
confidence: 99%